Superoxide anion radical scavenging property of catecholamines. (14th January 2013) - Kładna, Aleksandra; Berczyński, Paweł; Kruk, Irena; Michalska, Teresa; Aboul‐Enein, Hassan Y.
ABSTRACT: The direct effect of the four catecholamines (adrenaline, noradrenaline, dopamine and isoproterenol) on superoxide anion radicals ( O 2 − ) was investigated. The reaction between 18‐crown‐6‐ether and potassium superoxide in dimethylsulfoxide was used as a source of O 2 − . The reactivity of catecholamines with O 2 − was examined using chemiluminescence, reduction of nitroblue tetrazolium and electron paramagnetic resonance spin‐trapping techniques. 5, 5‐Dimethyl‐1‐pyrroline‐ N ‐oxide was included as the spin trap. The results showed that the four catecholamines were effective and efficient in inhibiting chemiluminescence accompanying the potassium superoxide/18‐crown‐6‐ether system in a dose‐dependent manner over the range 0.05–2 mm in the following order: adrenaline > noradrenaline > dopamine > isoproterenol, with, IC50 = 0.15 ± 0.02 mm 0.21 ± 0.03 mm, 0.27 ± 0.03 mm and 0.50 ± 0.04 mm, respectively. The catecholamines examined also exhibited a strong scavenging effect towards O 2 − when evaluated this property by the inhibition of nitroblue tetrazolium reduction (56–73% at 1m concentration). A very similar capacity of O 2 − scavenging was monitored in the 5, 5‐dimethyl‐1‐pyrroline‐ N ‐oxide spin‐trapping assay. The results suggest that catecholamines tested may involve a direct effect on scavenging O 2 − radicals. Copyright © 2013 John Wiley & Sons, Ltd.